Interaction of the Prominence Plasma within the Magnetic Cloud of an Interplanetary Coronal Mass Ejection with the Earth’s Bow Shock - Hadi Madanian; Li-Jen Chen; Jonathan Ng; Michael J. Starkey; Stephen A. Fuselier; Naoki Bessho; Daniel J. Gershman; Terry Z. Liu (The Astrophysical Journal)
The magnetic cloud within an interplanetary coronal mass ejection (ICME) is characterized by high magnetic field intensities. In this study, we investigate the interaction of a magnetic cloud carrying a density structure with the Earth’s bow shock during the ICME event on 2023 April 24. Elevated abundances of cold protons and heavier ions, namely, alpha particles and singly charged helium ions, associated with the prominence plasma are observed within this structure. The plasma downstream of the bow shock exhibits an irregular compression pattern, which could be due to the presence of heavy ions. Heavy ions carry a significant fraction of the upstream flow energy; however, due to their different mass-per-charge ratio and rigidity, they are less scattered by the electromagnetic and electrostatic waves at the shock. We find that downstream of the shock, while the ion thermal energy is only a small fraction of the background magnetic energy, nevertheless increased ion fluxes reduce the characteristic wave speeds in that region. As such, we observe a transition state of an unstable bow shock in which the plasma flow is super Alfvénic both upstream and downstream of the bow shock. Our findings help with the understanding of the intense space weather impacts of such events.